TEACHING ENGLISH THROUGH LITERARY DEVICES (Journal of Universal Science Research, 2023)
Literature plays an important role in teaching four basic language skills like reading, writing, listening and speaking. However, when using literature in the language classroom, skills should never be taught in isolation but in an integrated way. Teachers should try to teach basic language skills as an integral part of oral and written language use, as part of the means for creating both referential and interactional meaning, not merely as an aspect of the oral and written production of words, phrases and sentences.